The effect of exercise motivation on college students’ self-efficacy: the mediating roles of leisure satisfaction and mental toughness - Yu, Chengfeng; Zeng, Zhaohong; Xue, Aochuan; Wu, Qianjin (Frontiers in Psychology, 2024)
Background: The theory of motivation posits that individual motivation is moderately stimulated to drive individuals to engage in the behaviors for which they are motivated. It is therefore that the moderate stimulation of exercise motivation will inevitably lead to the enhancement of college students' participation in sports. Objective: investigate the impact of exercise motivation on college students' self-efficacy, reveal the mediating role of leisure satisfaction and mental toughness, and provide empirical evidence improving college students' self-efficacy through exercise motivation. Methods: A stratified whole-sample approach was employed to survey 715 college students, based on a correlation table with good reliability and validity. Scale items were designed to collect subjects' exercise motivation, self-efficacy, leisure satisfaction, and mental toughness in the study context. Mediation effect analyses were carried out using SPSS and AMOS. Results: a significant positive effect of exercise motivation on self-efficacy (β = 0.18, p < 0.001), leisure satisfaction (β = 0.50, p < 0.001), and mental toughness (β = 0.45, p < 0.001). Leisure satisfaction and mental toughness had a significant positive effect on self-efficacy (β = 0.40, p < 0.001; β = 0.30, p < 0.001). Furthermore, leisure satisfaction and mental toughness significantly mediated in exercise motivation and selfefficacy. In conclusion, our findings further explored the effects of exercise motivation on college students' self-efficacy and revealed the mediating roles of leisure satisfaction and mental toughness.